Peittymisongelma konenäön kontekstissa - Rautaniemi, Perttu (2019)
The problem of partial and total occlusion effects many different ﬁelds of machine vision implementation, and it has been effectively been solved using different algorithms. Core parts in the solving of this problem are different types of machine vision processors and the successful combining of the